The effects of leadership styles on employee performance: a case of a selected commercial bank in Botswana - Ushe Makambe; Gaone Joy Motlatsi Moeng (Annals of Management and Organization Research)
Purpose: The leadership phenomenon is fundamental in providing employees with direction and emotional indulgence to derive maximum effort out of them. Therefore, it is vital that an organisation places uninhibited emphasis on the appropriate leadership style to enhance employee performance. Premised on the Collaborative Leadership Model, this paper sought to extricate the nexus between leadership style and employee performance at a selected bank in Botswana, focusing on the transactional, transformational, and participative leadership styles. Research methodology: The study adopted a positivist research paradigm coupled with a survey research design, while a quantitative methodology was used to collect data through a self-administered questionnaire. The study population comprised 433 employees from which a sample of 200 was randomly selected. Data was analysed through the Statistical Package for Social Sciences (SPSS), culminating in statistical techniques such as factor analysis, regression analysis and Analysis of Variance (ANOVA). Results: The results of the study revealed that there was a significant utilisation of the participative, transformational, and transactional leadership styles at the selected commercial bank. However, while the use of the participative and transactional leadership styles had a positive and significant influence on employee performance, the transformational leadership style’s effect was insignificant. Limitation: The study only used quantitative data from employees for analysis and did not include bank leaders’ opinions. Contribution: The study contributed to the expansion of the body of knowledge on leadership style and employee performance in the banking sector in Botswana and elsewhere and helped to unmask the shortcomings of some styles while exposing the power of others in reaping positive reinforcements leading to enhancement of employee performance. Keywords: Leadership, Leadership style, Employee performance, Participative leadership, Transformational leadership, Transactional leadership